REKONSTRUKSI PENGATURAN PEMBATASAN PENDANAAN PARTAI POLITIK DALAM MENGATASI OLIGARKI YANG MENDISTORSI DEMOKRASI - Mihradi, R Muhammad (Jurnal Keadilan Pemilu, 2021)
Political parties are democracy's lifeblood. It is diffcult to envision a democracy without political parties. Political parties play an important strategic role. Political parties, in addition to facilitating public aspirations, are a source of recruitment for public offcials. as well as educating the general public about political education. The challenge is that political parties, including those in the financial sector, must be independent in order to play their roles effectively and without being partisan towards investors. In this context, restrictions on political party funding are required. Regulating party laws, unfortunately, has not been fully adequate in providing limits and strengthening accountability for political parties.